Corporate Law on Corporate Social Responsibility in the Perspective of John Rawls' Theory of Justice - Imtihani, Hajar; Arief Suryono; Tri Agus Suswantoro; Muhammad Nasser; Heridadi, Heridadi (Journal of Law, Politic and Humanities, 2024)
In the era of globalization and complex business environments, justice in Corporate Social Responsibility (CSR) is becoming increasingly important. CSR has become a central topic in the relationship between companies and society, focusing on social, environmental, and economic impacts. However, the main challenge lies in how to measure and apply the principles of justice in the implementation of CSR. This research will explore the application of John Rawls' Theory of Justice in the context of corporate social responsibility and its implementation in Indonesian regulations. Rawls' Theory of Justice, which emphasizes the fair distribution of resources and opportunities, is integrated into CSR regulations to create business practices oriented toward justice and sustainability. The research employs a normative juridical method using legal materials and a conceptual approach based on John Rawls' Theory of Justice. This study finds that while this theory provides a strong moral framework for companies in carrying out their social responsibilities, challenges arise in applying the principles of justice amid the complexities of the modern business world. This research offers concrete recommendations for companies and policymakers, including strengthening CSR regulations and enhancing transparency and stakeholder participation in corporate decision-making. The hope is that this research will contribute to shaping a more just and sustainable business environment in Indonesia.